Family migration and the path to an occupation: the (early) experiences of skilled Taiwanese and Chinese 'wives' - Hsu, Chieh (Taylor & Francis Group, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of illustrations -- Acknowledgements -- Preface -- PART 1: Placing women in the migration context -- 1. Professionals? Migrants? Wives? Who are these women? -- The hidden intersection of female skilled and family migration -- Distorted and reductionist lenses -- Research overview -- Research design and methodology -- Notes -- References -- 2. Women on and after the move -- Tied, love, and family female migration -- Women in mixed unions and intercultural families -- Adaptation into the host society -- Notes -- References -- 3. Home-country contexts vs. host-country realities -- The landscape of family migration in Germany -- Women's employment in Taiwan and China -- Immigrant (and native) women's employment in Germany -- Notes -- References -- PART 2: Understanding skilled "wives'" experiences -- 4. An evolving self tied to roles: Re-envisioning the immersion period -- Theories of integration and assimilation1 -- Symbolic interactionism and interactional role theory -- The post-arrival experience -- Re-envisioning the immersion period -- Note -- References -- 5. An insider's approach -- Researcher as member -- Constructivist grounded theory -- The narrative-discursive approach -- References -- PART 3: Navigating the new and bridging the gap -- 6. Marriage and dependency back home and in Germany -- Patriarchy, marriage, and female dependency in Taiwan and China -- Dependency experienced as a family migrant and a wife in Germany -- Latent classic patriarchy versus single-breadwinner model -- Notes -- References -- 7. Embracing dependency: Passive autonomy -- Defining passive autonomy -- Post-arrival self-realignment and work commitment in the case of passive autonomy -- Two extended vignettes -- Note -- References.
Description based on publisher supplied metadata and other sources